2018
DOI: 10.1051/e3sconf/20183702004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pyrolysis products derived from three biological wastes and their effect on plant growth and soil water retention

Abstract: Summary.Over two-thirds of Morocco can be classified as semiarid, arid and desert with low and variable rainfalls. While the country is subject to frequent drought, groundwater resources are predominantly consumed by irrigated agriculture leading to the depletion of water resources and degradation of soil quality. Application of bio-resources wastes to soils after pyrolysis process is well documented to help retain water and nutrients in soils. In this study, three bio-resources wastes derived from argan shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This changes the structure of the biochar and will invariably affect to what extent it can improve soil water retention. For example, Bouqbis et al (2018) reported that woodchip biochar tends to have a higher water holding capacity when added to soils than a blend of paper sludge and wheat husk biochar. To understand how biochar affects soil water properties we must understand the specific characteristics of biochar that influence these changes.…”
Section: Introductionmentioning
confidence: 99%
“…This changes the structure of the biochar and will invariably affect to what extent it can improve soil water retention. For example, Bouqbis et al (2018) reported that woodchip biochar tends to have a higher water holding capacity when added to soils than a blend of paper sludge and wheat husk biochar. To understand how biochar affects soil water properties we must understand the specific characteristics of biochar that influence these changes.…”
Section: Introductionmentioning
confidence: 99%
“…Although some have found that biochar increases soil water retention (de Duarte, Glaser, de Lima, & Cerri, 2019b; Kameyama, Miyamoto, & Shiono, 2014; Obia, Mulder, Martinsen, Cornelissen, & Børresen, 2016; Villagra‐Mendoza & Horn, 2018), others have not observed any significant difference in soil water retention with addition of biochar (Hardie, Clothier, Bound, Oliver, & Close, 2014; Jeffery et al, 2015; Wiersma, van der Ploeg, Sauren, & Stoof, 2020). These variations in observed results are largely due to the differences in biochar properties (Bouqbis et al, 2018; Mašek, Brownsort, Cross, & Sohi, 2013; Schnee, Knauth, Hapca, Otten, & Eickhorst, 2016; Sun, He, Pan, & Zhang, 2017). A meta‐analysis by Edeh, Mašek, and Buss (2020) showed that the biochar properties of great importance with respect to improvement of soil hydraulic properties are specific surface area, particle size and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Although some have found that biochar increases soil water retention (de Duarte, Glaser, de Lima, & Cerri, 2019b;Kameyama, Miyamoto, & Shiono, 2014;Obia, Mulder, Martinsen, Cornelissen, & Børresen, 2016;Villagra-Mendoza & Horn, 2018), others have not observed any significant difference in soil water retention with addition of biochar (Hardie, Clothier, Bound, Oliver, & Close, 2014;Jeffery et al, 2015;Wiersma, van der Ploeg, Sauren, & Stoof, 2020). These variations in observed results are largely due to the differences in biochar properties (Bouqbis et al, 2018;Mašek, Brownsort, Cross, & Sohi, 2013;Schnee, Knauth, Hapca, Otten, & Eickhorst, 2016;Sun, He, Pan, & Zhang, 2017). A meta-analysis by Edeh, Mašek, and Buss (2020) showed that the biochar properties of great importance with respect to improvement of soil hydraulic properties are specific surface area, particle size and porosity.…”
Section: Introductionmentioning
confidence: 98%